Physicochemical characterization and aerosol dispersion performance of organic solution advanced spray-dried cyclosporine A multifunctional particles for dry powder inhalation aerosol delivery - Wu X (International Journal of Nanomedicine, 2013)
Xiao Wu,1 Weifen Zhang,1,2 Don Hayes Jr,3–5 Heidi M Mansour1,61Department of Pharmaceutical Sciences – Drug Development Division, University of Kentucky, Lexington, KY, USA; 2College of Pharmacy and Biological Science, Weifang Medical University, Weifang, People's Republic of China; 3Department of Pediatrics, 4Department of Internal Medicine, The Ohio State University College of Medicine, Nationwide Children's Hospital Lung and Heart-Lung Transplant Program, 5Davis Heart and Lung Research Institute, The Ohio State University, Columbus, OH, 6Center of Membrane Sciences, University of Kentucky, Lexington, KY, USAAbstract: In this systematic and comprehensive study, inhalation powders of the polypeptide immunosuppressant drug – cyclosporine A – for lung delivery as dry powder inhalers (DPIs) were successfully designed, developed, and optimized. Several spray drying pump rates were rationally chosen. Comprehensive physicochemical characterization and imaging was carried out using scanning electron microscopy, hot-stage microscopy, differential scanning calorimetry, powder X-ray diffraction, Karl Fischer titration, laser size diffraction, and gravimetric vapor sorption. Aerosol dispersion performance was conducted using a next generation impactor with a Food and Drug Administration-approved DPI device. These DPIs displayed excellent aerosol dispersion performance with high values in emitted dose, respirable fraction, and fine particle fraction. In addition, novel multifunctional inhalation aerosol powder formulations of cyclosporine A with lung surfactant-mimic phospholipids were also successfully designed and developed by advanced organic solution cospray drying in closed mode. The lung surfactant-mimic phospholipids were 1,2-dipalmitoyl-sn-glycero-3-phosphocholine and 1,2-dipalmitoyl-sn-glycero-3-(phosphor-rac-1-glycerol). These cyclosporine A lung surfactant-mimic aerosol powder formulations were comprehensively characterized. Powder X-ray diffraction and differential scanning calorimetry confirmed that the phospholipid bilayer structure in the solid state was preserved following advanced organic solution spray drying in closed mode. These novel multifunctional inhalation powders were optimized for DPI delivery with excellent aerosol dispersion performance and high aerosol performance parameters.Keywords: dry powder inhaler (DPI), polypeptide drug, lung surfactant, calcineurin inhibitor, lung immunosuppression, dipalmitoylphosphatidylcholine (DPPC), dipalmitoylphosphatidylglycerol (DPPG), targeted lung immunosuppression